BLAMBANGAN PEOPLE'S RESISTANCE TO VOC YEAR 1767-1773 - Ahmad Ferdi Abdullah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2019)
This research is motivated to find out the extent of Blambangan people's struggle in dealing with voc using a qualitative research approach to the study of literature and interviews. the results of the study showed that the Blambangan kingdom suffered the consequences VOC power which tortures the people through its monopil, this is the cause of people's resistance. To be able to answer that problem, this study aims to describe the resistance of the people of Blambangan against the VOC in 1767 1773. Specifically, this study aims to find out (1) the people of Blambangan make a fight against the VOC. (2) the factors that caused the people of Blambangan to resist the VOC. (3) the impact of resistance to the VOC in Blambangan. To achieve these research objectives, the research method that I use is a type of historical research with data collection techniques through library research sourced from books, documentation and observations. Meanwhile, to analyze the data the authors used source criticism techniques both externally and internally, after that the authors conducted the analysis. From the results of this analysis the authors reference in answering the problems in this study. The results of the study showed that the Blambangan Rakyat Resistance was led by two great figures of his time, who had many followers, namely Wong Agung Willis and Mas Rempeg (Jagapati). Agung Willis's position in Blambangan became stronger when Mas Anom and Mas Weka, two Blambangan regents appointed by the Company decided to join him, the Dutch expected Blambangan to increase because ethnic Chinese and Bugis joined him, with this power the resistance succeeded in winning even though in the end Agung Willis was captured and Mas Rempeg was injured and later died.